Adenosine and inflammation: CD39 and CD73 are critical mediators in LPS-induced PMN trafficking into the lungs - Reutershan, Joerg; Vollmer, Irene; Stark, Stefanie; Wagner, Rosalyn; Ngamsri, Kristian-Christos; Eltzschig, Holger K. (The FASEB Journal, 2009)
Extracellular adenosine has been implicated as anti-inflammatory signaling molecule during acute lung injury (ALI). The main source of extracellular adenosine stems from a coordinated two-step enzymatic conversion of precursor nucleotides via the ectoapyrase (CD39) and the ecto-5′-nucleotidase (CD73). In the present study, we hypothesized a critical role of CD39 and CD73 in mediating pulmonary neutrophil (PMN) transmigration during lipopolysaccharide (LPS)-induced lung injury. Initial studies revealed that pulmonary CD39 and CD73 transcript levels were elevated following LPS exposure in vivo. Moreover, LPS-induced accumulation of PMN into the lungs was enhanced in cd39 -/- or cd73-/- mice, particularly into the interstitial and intra-alveolar compartment. Such increases in PMN trafficking were accompanied by corresponding changes in alveolar-capillary leakage. Similarly, inhibition of extracellular nucleotide phosphohydrolysis with the nonspecific ecto-nucleoside-triphosphate-diphosphohydrolases inhibitor POM-1 confirmed increased pulmonary PMN accumulation in wild-type, but not in gene-targeted mice for cd39 or cd73. Finally, treatment with apyrase or nucleotidase was associated with attenuated pulmonary neutrophil accumulation and pulmonary edema during LPS-induced lung injury. Taken together, these data reveal a previously unrecognized role for CD39 and CD73 in attenuating PMN trafficking into the lungs during LPS-induced lung injury and suggest treatment with their soluble compounds as a therapeutic strategy. © FASEB.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acute lung injury; ARDS; Chemotaxis; Migration; Neutrophil; PMN